2022
DOI: 10.15835/nbha50112590
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of broad-spectrum biocontrol efficacy of Bacillus velezensis against Fusarium oxysporum in Triticum aestivum L.

Abstract: Fungi are the most important phytopathogens that cause yield losses. The mycotoxins released by fungi cause spoilage of stored food consumed by humans and feed supplied to animals. Fungi-antagonistic microbes are gaining attention as potential biocontrol agents (BCAs). This study was designed to isolate bacterial isolates from different crops and evaluate their in vitro antifungal assay against three phytopathogens, plant growth promoting (PGP) characteristics, molecular identification, and in vivo efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Debbi et al (2018) verified that PGPR are beneficial bacteria that can colonize and promote plant growth, and inhibit or reduce the threat of plant diseases (Sarwar et al, 2020). Tests have indicated that plant rhizosphere bacteria can promote the dissolution of phosphorus and potassium, inhibit pathogen, improve stress resistance, and produce IAA and other plant hormones, thereby increasing crop yields (Agha et al, 2022). The study of PGPR, mainly including Mesorhizobium and Allorhizobium, intracellular PGPR, and Bacillus, Pseudomonas and Azotobacter extracellular PGPR (Li et al, 2020), has attracted the attention of scholars at home and abroad.…”
Section: Discussionmentioning
confidence: 90%
“…Debbi et al (2018) verified that PGPR are beneficial bacteria that can colonize and promote plant growth, and inhibit or reduce the threat of plant diseases (Sarwar et al, 2020). Tests have indicated that plant rhizosphere bacteria can promote the dissolution of phosphorus and potassium, inhibit pathogen, improve stress resistance, and produce IAA and other plant hormones, thereby increasing crop yields (Agha et al, 2022). The study of PGPR, mainly including Mesorhizobium and Allorhizobium, intracellular PGPR, and Bacillus, Pseudomonas and Azotobacter extracellular PGPR (Li et al, 2020), has attracted the attention of scholars at home and abroad.…”
Section: Discussionmentioning
confidence: 90%
“…We isolated about 180 bacteria from rhizosphere of different crops and tested it for antagonistic activity against F. oxysporum using dual culture plate assay. The dual culture plate assay is a popular method for testing biocontrol activity against fungi [ 8 , 34 , 35 ]. The threshold activity was maintained at 70% antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus genus bacteria have been shown to perform well as biocontrol agents (BCAs) due to their ability to produce a wide range of molecules capable of inhibiting fungal growth [ 7 ]. Agha et al [ 8 ] demonstrated that B. Velezensis RC 218 bioformulate was effective in reducing Fusarium head blight caused by F. graminearum in green house and field conditions in wheat cultivar. Jangir et al [ 9 ] showed the consortium of B.subtilis and T. harzianum not only suppresses Fusarium wilt in S. lycopersicum but also improves soil health.…”
Section: Introductionmentioning
confidence: 99%
“…Some components of phyllosphere microorganisms can cause plant diseases, and even lead to poisoning, allergy and infection reactions in humans and animals [ 1 , 2 ]. Using the beneficial functions of the phyllosphere microorganisms to promote plant growth is a sustainable solution [ 2 , 3 , 4 , 5 , 6 , 7 ]. In agricultural ecosystems, the biological potential of beneficial bacteria (biocontrol bacteria, plant growth hormone producing bacteria and azotobacter, etc.)…”
Section: Phyllospheric Microbial Functionmentioning
confidence: 99%
“…Moreover, phyllosphere functional traits can be regulated by phyllosphere microorganisms to improve plant adaptability. This will help reduce fertilizer and pesticide input, promote plant growth and reduce environmental pollution, and thus achieve high-quality agricultural development [ 2 , 3 , 4 , 5 , 6 , 7 ]. As important phyllosphere microorganisms, Methylobacterium spp., Sphingomonas spp., Pseudomonas spp., etc., are all potential beneficial bacteria, whereas Alternaria spp., Fusarium spp., etc., are potential pathogens.…”
Section: Phyllospheric Microbial Functionmentioning
confidence: 99%